G133.50+9.01: a likely cloud–cloud collision complex triggering the formation of filaments, cores, and a stellar cluster. Issue 3 (6th October 2020) - Issac, Namitha; Tej, Anandmayee; Liu, Tie; Wu, Yuefang
ABSTRACT: We present compelling observational evidence of G133.50+9.01 being a bona fide cloud–cloud collision candidate with signatures of induced filament, core, and cluster formation. The CO molecular line observations reveal that the G133.50+9.01 complex is made of two colliding molecular clouds with systemic velocities, $\rm -16.9$ and $\rm -14.1\, km\, s^{-1}$ . The intersection of the clouds is characterized by broad bridging features characteristic of collision. The morphology of the shocked layer at the interaction front resembles an arc-like structure with enhanced excitation temperature and H2 column density. A complex network of filaments is detected in the Submillimeter Common-User Bolometer Array 2 850 $\rm μ m$ image with 14 embedded dense cores, all well correlated spatially with the shocked layer. A stellar cluster revealed through an overdensity of identified Classes I and II young stellar objects is found located along the arc in the intersection region corroborating with a likely collision induced origin.